Pathophysiology and targets for treatment in hereditary galactosemia: A systematic review of animal and cellular models. Issue 3 (14th January 2020) - Haskovic, Minela; Coelho, Ana I.; Bierau, Jörgen; Vanoevelen, Jo M.; Steinbusch, Laura K. M.; Zimmermann, Luc J. I.; Villamor‐Martinez, Eduardo; Berry, Gerard T.; Rubio‐Gozalbo, M. Estela
Abstract: Since the first description of galactosemia in 1908 and despite decades of research, the pathophysiology is complex and not yet fully elucidated. Galactosemia is an inborn error of carbohydrate metabolism caused by deficient activity of any of the galactose metabolising enzymes. The current standard of care, a galactose‐restricted diet, fails to prevent long‐term complications. Studies in cellular and animal models in the past decades have led to an enormous progress and advancement of knowledge. Summarising current evidence in the pathophysiology underlying hereditary galactosemia may contribute to the identification of treatment targets for alternative therapies that may successfully prevent long‐term complications. A systematic review of cellular and animal studies reporting on disease complications (clinical signs and/or biochemical findings) and/or treatment targets in hereditary galactosemia was performed. PubMed/MEDLINE, EMBASE, and Web of Science were searched, 46 original articles were included. Results revealed that Gal‐1‐P is not the sole pathophysiological agent responsible for the phenotype observed in galactosemia. Other currently described contributing factors include accumulation of galactose metabolites, uridine diphosphate (UDP)‐hexose alterations and subsequent impaired glycosylation, endoplasmic reticulum (ER) stress, altered signalling pathways, and oxidative stress. galactokinase (GALK) inhibitors, UDP‐glucose pyrophosphorylase (UGP) up‐regulation, uridine supplementation, ER stress reducers, antioxidants and pharmacological chaperones have been studied, showing rescue of biochemical and/or clinical symptoms in galactosemia. Promising co‐adjuvant therapies include antioxidant therapy and UGP up‐regulation. This systematic review provides an overview of the scattered information resulting from animal and cellular studies performed in the past decades, summarising the complex pathophysiological mechanisms underlying hereditary galactosemia and providing insights on potential treatment targets.